Impact of hydrophilic emulsifier and emulsion microstructure on aroma release over w/o/w emulsions - Pu, Xiaolu (2018)
In this thesis, the impact of the interactions between the hydrophilic emulsifiers and aroma compounds as well as emulsion microstructure including droplet size, droplet size distribution, emulsion stability and creaming on aroma release over water-in-oil-in-water (w/o/w) emulsions was investigated. Polyglycerol polyricinoleate (PGPR) was used as the only hydrophobic emulsifier to stabilise the internal water droplets in the primary water-in-oil (w/o) emulsion of the w/o/w emulsions throughout this research. Three hydrophilic emulsifiers investigated to stabilise the w/o droplets in w/o/w emulsions included a low molecular weight non-ionic surfactant, polyoxyethylene 20 sorbitan monolaurate (Tween 20), a chemically modified starch, octenyl succinic anhydride (OSA) starch and a protein, pea protein isolate (PPI), as the large molecular weight emulsifiers. The two emulsification methods of high shear mixing and stirred cell membrane emulsification were used. Controls of water and oil-in-water (o/w) emulsions were prepared with the formulation and process conditions as for the w/o/w emulsions. Emulsion microstructure was characterised in terms of droplet appearance, droplet size, droplet size distribution as well as emulsion stability over time. Both static and dynamic headspace analyses were carried out to investigate the aroma release behaviour over w/o/w emulsions. The results showed that w/o/w emulsions were a suitable vehicle for short time aroma entrapment, which was most successful for the hydrophilic aroma acetoin compared to the hydrophobic aromas acetyl pyridine and hexanal. This entrapment of the hydrophilic aroma resulted from the barrier of the oil phase in the w/o droplets to delay its diffusion or the PGPR micelles in the oil phase to entrap it in the polar inner core. The complex food emulsifiers OSA starch and PPI were for the first time successfully used in stirred cell membrane emulsification to produce similarly sized o/w and w/o/w emulsions. These were produced to eliminate the effect of droplet size in the study of aroma release. The release of aromas (i.e. diacetyl and 3-pentanone) was affected by the combination of the type of the hydrophilic emulsifier (Tween 20, OSA starch and PPI) and the type of the emulsion system (i.e. o/w and w/o/w emulsions) as well as the emulsion microstructure including droplet size, emulsion stability, interface thickness, creaming and diffusion of the internal water phase into the external water phase of w/o/w emulsions. The thinner interface laden by Tween 20 might lead to a quicker diffusion of the hydrophobic aroma 3-pentanone from the w/o droplets into w2. OSA starch interacted with the hydrophilic aroma diacetyl and 3-pentanone, and PPI interacted with 3-pentanone. These findings help to better understand the effect of the hydrophilic emulsifier and emulsion microstructure on aroma release and present a novel study to produce similarly sized emulsion droplets with complex food emulsifiers.